As pecularidades da violência no Ceará: aventuras e maneiras de fazer o crime - Sousa, Manoel Johnson Sales (2019)
This work is the product of an effort to understand the peculiarities and ways of making crime in Ceará. Through critical reading of previous productions that approach the same theme, consulting various materials such as newspaper articles and internet sites, making use of analytical tools such as music, TV series, comics and other expressions of pop culture, and mainly through deep immersion in the empirical field, having "participant observation", the conversations in the "mouths", parties and places of action of factionalists, and semi-structured interviews as main techniques, thus reaching a theoretical-methodological path that aims to reach the socio-historical-cultural elements and the factors involved in the production of the subjectivities of young people who are part of the criminal movement, identifying psychosocial characteristics and recurrent and common behaviors in the ways of practicing crime in Ceará, distinguishing, together with the individuals surveyed, a "Cearense way of doing". The options and renunciations made by young residents of the peripheries and engaged in crime were observed and what they understood as ethical, moral, cultural, economic and social consequences of their choices, considering details of behavior as, the new expressions of intimacies that occur through asymmetric relations, in which money and power, of illicit origin, foment relationships that both challenge and reinforce and resignify existing moral standards. The fragmentation, intensification of territorial disputes and violent spectacularisation through torture, slaughter and public demonstrations of cruelty are understood as characteristics of a scenario in which the monopoly of violence is being fought with the State and the demonstrations of force function as element of deterrence and affirmation of criminal collectives. The study carried out in communities located in the municipalities of Itapajé, Paraipaba, Caucaia and Fortaleza, sought to go beyond the objective and material questions and to advance to the cultural aspects of the phenomenon, concluding that among the interviewees, the conflicts, ethical arrangements and rearrangements, that allow the development of sociabilities that now defy, and reaffirm and to resignify the dominant morality, accommodating contradictory and conflicting ways of perceiving and acting in society, founded a lifestyle based on crime, offering for young people from the peripheries, identities, options of socioeconomic inclusion and the sense of resistance against the established order.